Kontemplasi dan Analisis Hukum Terhadap Penanganan Eksploitasi Seksual Komersial Anak di Indonesia - Nurafni Nurafni; Topo Santoso (Nagari Law Review, 2022)
The problem of commercial sexual exploitation of children is a serious problem and is not a new problem that has emerged recently. This crime has been happening for a long time and has been experienced by many countries, including Indonesia. For a long time, the Indonesian government has made various efforts to minimize the increase in the types of crimes that attack the future of children, such as by issuing several policies. However, day by day this crime is getting more and more victims. Moreover, with the development of an increasingly sophisticated era, this criminal activity is growing. With technological capabilities that facilitate the modus operandi of perpetrators, it certainly raises its own concerns in protecting children from sexual exploitation for commercial purposes. This research is a socio-legal research using secondary data consisting of primary, secondary and tertiary legal materials collected through the study of library materials then analyzed qualitatively and presented descriptively so as to obtain a detailed and systematic description of the description of the crime of commercial sexual exploitation of children. divided into several periods and the development of its handling in Indonesia.